Immunophenotypic variations in syphilis: insights from Mendelian randomization analysis - Xie, Qinghui; Tang, Yijie; Shen, Lingyun; Yang, Dandan; Zhang, Jiaqin; Luo, Qingqiong (Frontiers in Immunology, 2024)
Background: Infection with Treponema pallidum instigates complex immune responses. Prior research has suggested that persistent Treponema pallidum infection can manipulate host immune responses and circumvent host defenses. However, the precise role of immune cells in Treponema pallidum infection across different stages remains a contentious issue.Methods: Utilizing summary data from genome-wide association studies, we employed a two-sample Mendelian randomization method to investigate the association between 731 immunophenotypes and syphilis. Syphilis was categorized into early and late stages in this study to establish a more robust correlation and minimize bias in database sources.Results: Our findings revealed that 33, 36, and 27 immunophenotypes of peripheral blood were associated with syphilis (regardless of disease stage), early syphilis and late syphilis, respectively. Subsequent analysis demonstrated significant variations between early and late syphilis in terms of immunophenotypes. Specifically, early syphilis showcased activated, secreting, and resting regulatory T cells, whereas late syphilis was characterized by resting Treg cells. More B cells subtypes emerged in late syphilis. Monocytes in early syphilis exhibited an intermediate and non-classical phenotype, transitioning to classical in late syphilis. Early syphilis featured naive T cells, effector memory T cells, and terminally differentiated T cells, while late syphilis predominantly presented terminally differentiated T cells. Immature myeloid-derived suppressor cells were evident in early syphilis, whereas the dendritic cell immunophenotype was exclusive to late syphilis.Multiple immunophenotypes demonstrated associations with syphilis, showcasing substantial disparities between the early and late stages of the disease. These findings hold promise for informing immunologically oriented treatment strategies, paving the way for more effective and efficient syphilis interventions.